Fabrication and tribological behaviors of corner-cube-like dimple arrays produced by laser surface texturing on medical needles. (December 2015) - Wang, Xingsheng; Giovannini, Marco; Xing, Youqiang; Kang, Min; Ehmann, Kornel
Abstract: Micro-corner-cube-like dimples with various geometrical characteristics were fabricated on the surface of medical needles by laser surface texturing. The effects of geometric parameters of dimples on tribological behaviors were investigated by carrying out insertion tests. It was found that the textured surface with a dimple array increased the friction between the needle and phantom tissue because of stress concentrations near the edges. Furthermore, the drag increment rate increased with the increase of dimple size and circumferential number, while dimple depth had no significant effect on the friction. The minimal drag increment rate was achieved at a medium value of spacing. The geometric parameters of dimples could be varied to control area density that indirectly affect the friction behavior. Highlight: The textured surface increases the friction because of the edge effect of dimples. The friction increases with the increase of dimple size and circumferential number. Dimple depth has no significant effect on the friction. The minimal friction is achieved at a medium value of spacing. The effect of area density on the friction has some indirect character.